Targeting glial B2-adrenoceptors for immunododulation & neuoprotection in a rat model of Parkinson's disease - O'NEILL, EOIN (Trinity College Dublin. School of Pharmacy & Pharma. Sciences. Discipline of Pharmacy, 2019)
Neuro-inflammation is a key contributor to the pathogenesis of Parkinson’s disease (PD). Brain-resident microglia are dynamic cellular effectors of inflammation-mediated neurodegeneration in the Parkinsonian brain. Here we have established & characterised an inflammation-mediated preclinical animal model of experimental PD by direct infusion of the bacterial endotoxin, and TLR4 agonist, lipopolysaccharide (LPS) directly into the SNpc of adult male Wistar rats. Unilateral intra-nigral injection of LPS (10μg/2μl) induced robust Iba1 + microglial activation, tyrosine hydroxylase-positive (TH + ) dopamine cell loss in the substantia nigra pars compacta (SNpc), TH + striatal denervation and nigrostriatal dopamine depletion as verified by high performance liquid chromatography with electrochemical detection (HPLC-ECD), findings which were accompanied by deficits in skilled motor function in the staircase test, forelimb use asymmetry in the cylinder test and bidirectional forelimb akinesia in the stepping test. Moreover, we simultaneously co-administered the astroglial-selective toxin L-alphaaminoadipic acid to investigate whether a more populous, yet majorly overlooked glial subtype known as astrocytes contribute towards, or protect against an intra-nigral LPSinduced Parkinsonian state. Here we show that transient GFAP + astrocytic dysfunction limits the severity & delays the progression of intra-nigral LPS-induced Iba1 + microgliosis, TH + dopaminergic neurodegeneration, nigrostriatal dopamine loss and ensuing motor dysfunction. Our data demonstrates a role for reactive astrocytes in actively sustaining LPS-induced midbrain microglial activation and contributing towards dopaminergic neuronal loss and experimental Parkinsonism, at least in part via the release of soluble factors such as S100β. Here we propose an indelible neurotoxic role for astrocytic crosstalk with midbrain microglia at the interface of intra-nigral LPS-mediated dopaminergic neuropathology, thus spotlighting astrocytes as dark horses of inflammation-mediated neurodegeneration in the Parkinsonian brain. To this end we sought to investigate whether targeting the noradrenergic system for anti-inflammatory & neuroprotective effects via glial cell immunomodulation and neurotrophic factor production could protect against LPS-mediated neurotoxicity of the nigrostriatal dopaminergic tract. Twice daily treatment with the noradrenaline reuptake inhibitor atomoxetine (3 mg/kg i.p.) alone or in combination with the α2-adrenoceptor antagonist idazoxan (1 mg/kg i.p.) for 7 days commencing 4 hours post lesioning, attenuates intra-nigral LPS-mediated Iba1 + microglial activation & TH + dopaminergic neuronal loss, ameliorates nigrostriatal dopamine depletion and provides partial protection against associated motor deficits. These findings demonstrate that pharmacologically enhancing noradrenergic tone exerts anti-inflammatory effects in the inflamed midbrain, and protects against LPS-mediated neurotoxicity of the nigrostriatal dopaminergic tract, thus facilitating motor improvements at least in part via immunomodulation of nigral microglia. Akin to the greater susceptibility of the elderly population to the detrimental effects of a bacterial infection, we further examined the impact of superimposing an exposure to a peripheral immune stressor on pre-existing intra-nigral LPS-mediated microglial activation, dopaminergic neurodegeneration & motor dysfunction. Here we show that a sub-toxic, low dose of systemic LPS (250 μg/kg i.p.) exacerbates ongoing TH + dopamine cell loss in the SNpc, augmented nerve terminal degeneration in the striatum and exaggerated ensuing motor deficits, findings which were underpinned by an expansion in nigral Iba1 + microgliosis, increases in CD68 expression and elevations in nigral IL-1β production. Moreover treatment with formoterol, a long acting, lipophilic and highly selective β 2 -adrenoceptor agonist curtailed microglial activation in the SN and prevented exacerbations in the degeneration of the nigrostriatal dopaminergic tract, thus attenuating the exaggerated deficits in motor function. These findings indicate that an acute episode of a systemic bacterial infection can accelerate neurodegenerative disease progression, whereas pharmacologically targeting β 2 -AR’s directly could slow/halt the progression of Parkinsonian neuropathology & symptomology in instances where inflammation contributes to disease pathogenesis. Taken together, the data gathered herein highlights midbrain glia (both microglia & astrocytes) as crucial cellular effectors of immune-mediated dopaminergic neurodegeneration in the Parkinsonian brain, and promotes pharmacologically targeting the CNS noradrenergic system for anti-inflammatory and neurotrophic effects to provide neuroprotection against inflammation-mediated neurotoxicity, nigrostriatal dopamine loss and motor dysfunction.
APPROVED
Keywords: Neuro-inflammation; Parkinson's disease